Indonesia’s Village Fiscal Transfers (Dana Desa) Policy: The Effect On Local Authority And Resident Participation - KHAIRULLAH ANSHARI (Universitas Muhammadiyah Yogyakarta, 2018)
According to Indonesia Village Law 6/2014, village fiscal transfer policies provide exclusive funds from the national government to the Dana Desa, adding to the existing amended contribution funding from regency to village. This paper discusses how this fiscal transfer policy for rural development affects local authority transfers to villages and residents’ participation in development. By using a case study method in Banjar Regency, South Kalimantan Province with qualitative surveys in villages and interviews, this article makes a number of remarks. Firstly, the paper comments on the authority transfer from the regency to the villages in public works, agriculture, pre-school education, and community-based health services. The projects discussed are characterized as infrastructure priorities, community-based operations, and non-complex. Banjar Regency agencies have accepted this authority transfer because of budget limitations for village-level projects. The authority transfer has resulted in changes in the Regency’s character from a village-level public service provider to an adviser. Secondly, the paper discusses residents’ participation in village development. Village fiscal transfers are used mostly in village development projects, where local preferences are accommodated; accordingly, the community participates in the planning and executing of those projects. However, accountability still must be improved despite the perception of the corruption indication assumption being low.